Maternal Preconception Omega-6, Omega-3, and Omega-6:Omega-3 Intake and Uterine Artery Indices in Mid-Gestation - Finch, Amara; Joss-Moore, Lisa; Allshouse, Amanda A.; Blue, Nathan; Haas, David M.; Grobman, William; Parry, Samuel; Saade, George; Silver, Robert M. (American Journal of Perinatology, 2024)
Objective Maternal preconception diet influences pregnancy health and fetal outcomes. We examined the relationship between preconception fatty acid (FA) intake and uterine artery indices in mid-gestation in a large, heterogeneous cohort of nulliparous individuals.Study Design This is a secondary analysis of the nuMom2b (Nulliparous Pregnancy Outcomes Study: Monitoring Mothers-to-be) study. Dietary ω-6 and ω-3 FA intake was assessed with food frequency questionnaires and uterine artery indices were obtained via Doppler studies in the second trimester. For our primary outcome of pulsatility index (PI) > 1.6, we compared proportions by each dichotomous FA exposure and tested differences with chi-square test.Results For PI > 1.6, odds ratio for the unfavorable FA quartile compared with remaining quartiles for the exposures were 0.96 to 1.25, p = 0.157 (ω-6 FA); 0.97 to 1.26, p = 0.124 (ω-3 FA); 0.87 to 1.14, p = 1.00 (ω-6:ω-3 FA ratio).Conclusion No significant associations between self-reported maternal preconception ω-6 and ω-3 FA intake and uterine artery Doppler indices measured during the second trimester were observed.Key Points
Keywords: maternal nutrition; essential fatty acids; fetal development; periconception health; uterine artery blood flow